Evaluation of Clinical Skills of Nurses in Coronary Care Units of Affiliated Hospitals of Tehran University of Medical Sciences and Health Services - M. Mahmoody; N. Zakeri moghadam; Z. Parsa yekta; N. Dehghan naeiri (Tehran University of Medical Sciences, 1999)
This study is a descriptive -analytical research which is designed to evaluate clinical skills of Nurses in coronary care units in affiliated hospitals of Tehran medical sciences University.The specific objectives of this research are as follows: Determining clinical skills of nurses in coronary care unit in the fields of patient assessment, intrepretation of Electrocardiogram, and ABG test administration, Iv therapy, educating the clients , caring the patients under cardiac catheterization and resuscitation ofcardio-pulmonary disorders. The population involved 50 nurses who were working in the coronary care units. The sample and population were the same. The researcher collected the data during a period of 3 months and observed the subjects minimum two full working shifts.The results indicated that nursing skills of the majority of the subjects towards the patient"nassessment was at weak level, one half of them had high level skill ofEKG interpretation"n(+90%), Meanwhile 2/3 of the subjects (68%) had a very weak skill (0-20%) in the field of ABG"ntest interpretation. One half of them had a medium skill for administration ofthe IV drug"ntherapy and all of them were at very weak level for patient education skills. More than one half"nof these nurses had a good skill about nursing care of the patients under cardiac"ncatheterization. Finally, the last objective (Cardiac resuscitation skill) was not analysed due to a"nfew cases.